Determination and Application of Improved Kinetic Parameters for Simulation of Maleic Anhydride Synthesis in Industrial Fixed- Bed Reactor - Ervin Karić; Ivan Petric; Vladan Mićić (Journal of Engineering & Processing Management, 2019)
The aims of this study were to determine improved kineticparameters in five kinetic models for oxidation of n-butane intomaleic anhydride in an industrial fixed-bed reactor, and tosimulate the reactor performance. On the basis of the measuredprocess parameters, inlet and outlet concentrations of n-butanewere calculated and then used to fit the kinetic models. Theindustrial fixed-bed reactor was approximated by 10 continuousstirred tank reactors (CSTR) connected in series. Based on thecalculated outlet concentration of n-butane from the industrialreactor, the outlet concentration of n-butane from thepenultimate reactor was calculated. Then the concentrations ofn-butane were calculated until the inlet concentration of nbutanein the first reactor was obtained. Kinetic parameterswere determined by comparing the inlet concentrations of nbutanein the first reactor with the inlet concentration of nbutaneobtained on the basis of the measured processparameters in the industrial fixed-bed reactor. Kinetic modelswith improved kinetic parameters showed better simulationresults compared to kinetic models with the existing kineticparameters. The best agreement of simulation results andmeasured values was achieved with application of the kineticmodel 2 (Equations (2a-c)). The smallest deviations ofnumerical simulation in comparison with measured values of theoutlet pressure of reaction mixture were 0.45, 0.75 and 0.75%for application of the kinetic model 3 (Equations (3a-c)). Thepercentage deviations of numerical simulation with improvedkinetic parameters and the existing kinetic parameters incomparison with measured values of inside reactor temperaturewere in the range 0.90-5.36% and in the range 4.17-9.78%(kinetic model 2, Equations (2a-c)), respectively.
Keywords: kinetic parameters; kinetic models; maleic anhydride; simulation; fixed-bed reactor